Study On Nutritional Disorders Among School Going Children In A South Indian City - DR.PAVAN KUMAR KULKARNI; DR.MASEER KHAN (International Journal of Pharma and Bio Sciences, 2012)
According to survey by FAO [2006) (1) on one side there is still prevalence of malnutrition and other deficiency diseases like anaemia, vitamin A and iodine deficiency, improper immunization and food insecurity, while on the other side overweight and obesity are rampant among children in India. The consequences of underweight and deficiency diseases as well as overweight and obesity are extensive among children, resulting in reduction in the rate of productivity. The study included a sample of 1575 matriculation school children aged six to fifteen years that included 20% children from each grade (one-ten) and 25% children from each area and from each socioeconomic strata (urban with high, middle and low SES and rural with low/disadvantaged SES).The selection was based on random sampling technique with the teachers allotting the students as per the roll order on a random basis. Common deficiency diseases prevalent among the school going children were Vitamin A deficiency, anaemia and skin infections. Among the deficiency symptoms, as diagnosed through clinical examination by a physician, anaemia was predominant in 650 (70.2%) of preadolescent girls. The prevalence of obesity is more among adolescent boys (24.2%) than adolescent girls ( 23.3%). In the adolescent age group of 12-16 years, 12 boys from matriculation schools were found to have elevated blood pressure, both systolic and diastolic, while among girls six from matriculation schools were found to have high blood pressure.